Hereditary hyperferritinemia-cataract syndrome in a family with HFE-H63D mutation - YANIK, AHMET MERT; YILMAZ, ASU FERGÜN; TOPTAŞ, TAYFUR (My University, 2023)
Hereditary hyperferritinemia-cataract syndrome (HHCS) is a rare genetic condition characterized by persistent hyperferritinemia (usually ferritin >1,000 ng/mL) without tissue iron overload, with or without early-onset slow-progressing bilateral nuclear cataract. It was first identified as a new genetic disorder in 1995, and since then genetic sequencing studies have been carried out to identify associated mutations in affected families. New mutations around the world are still being reported in the iron-responsive element (IRE) of the L-ferritin gene (FTL) to this day. Many clinicians remain unaware of this rare condition. The co-occurrence of FTL mutations and hereditary hemochromatosis (HH) mutations, especially H63D, on the HFE gene has been reported in the literature, which often leads to a diagnosis of HH, missed diagnosis of HHCS, incorrect treatment with phlebotomies and the occurrence of associated iatrogenic iron deficiency anemia. We herein report the case of a 40-year-old woman with spontaneous facial freckling, bilateral cataracts, homozygosity for HFE H63D mutation, iron deficiency anemia, and hyperferritinemia, who has been treated with phlebotomy and iron chelation therapy to no avail. Eleven years after being diagnosed and treated for HH, a reevaluation of her clinical presentation, laboratory results, medical imaging, and family history led to the recognition that her case is explained not by HH, but by an alternative diagnosis, HHCS. Our main objective in this report is to increase clinical awareness about HHCS, an often-unknown differential diagnosis of hyperferritinemia without iron overload, and to prevent adverse medical interventions in HHCS patients.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; TIP, GENEL & DAHİLİ; Klinik Tıp; Klinik Tıp (MED); MEDICINE, GENERAL & INTERNAL; CLINICAL MEDICINE; Clinical Medicine (MED); Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Dahiliye; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Internal Medicine; Family Practice; Medicine (miscellaneous); General Medicine; ferritin; cataract; hereditary hemochromatosis; hyperferritinemia; hereditary hyperferritinemia-cataract syndrome; FERRITIN; GENE; ferritin; cataract; hereditary hemochromatosis; hyperferritinemia; hereditary hyperferritinemia-cataract syndrome